2021
DOI: 10.1080/15548627.2021.1962681
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-VDR (vitamin D receptor) regulates defective autophagy in renal tubular epithelial cell in streptozotocin-induced diabetic mice via the AMPK pathway

Abstract: Zhang (2021): Vitamin D-VDR (vitamin D receptor) regulates defective autophagy in renal tubular epithelial cell in streptozotocin-induced diabetic mice via the AMPK pathway, Autophagy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 47 publications
6
65
0
1
Order By: Relevance
“…PCV2 induces autophagy via the CaMKKβ-AMPK pathway in pig kidney PK-15 cells by increasing cytosolic Ca 2+ [113]. Activation of vitamin D receptors can restore defective autophagy through the Ca 2+ -CAMKKβ-AMPK pathway in renal tubular epithelial cells in streptozotocin-induced diabetic mice [114]. Ca 2+ signaling is involved in AMPK-mediated autophagy, and plays a role in coordinating cellular survival and kidney function.…”
Section: Targeted Ca 2+ Signaling For Therapy Of Kidney Diseasesmentioning
confidence: 96%
See 1 more Smart Citation
“…PCV2 induces autophagy via the CaMKKβ-AMPK pathway in pig kidney PK-15 cells by increasing cytosolic Ca 2+ [113]. Activation of vitamin D receptors can restore defective autophagy through the Ca 2+ -CAMKKβ-AMPK pathway in renal tubular epithelial cells in streptozotocin-induced diabetic mice [114]. Ca 2+ signaling is involved in AMPK-mediated autophagy, and plays a role in coordinating cellular survival and kidney function.…”
Section: Targeted Ca 2+ Signaling For Therapy Of Kidney Diseasesmentioning
confidence: 96%
“…Saikosaponin-d (SSd), a SERCA inhibitor, suppresses excess ER Ca 2+ reuptake and cell proliferation in ADPKD cells by inducing autophagy through the CaMKKβ-AMPK-mTOR signaling pathway, which indicates that SSd might be a potential treatment for ADPKD and that SERCA might be a novel target for ADPKD therapy [117]. It has been reported that AMPK activation restored the defective autophagy in high glucose-induced HK-2 cells [114]. Activators of CaSR such as cinacalcet have renoprotective effects in high glucose-treated human glomerular endothelial cells, murine podocytes and diabetic mice.…”
Section: Targeted Ca 2+ Signaling For Therapy Of Kidney Diseasesmentioning
confidence: 99%
“…Several animal studies have shown that 25(OH)D 3 concentrations are significantly lower in DN compared to healthy controls, suggesting that vitamin D plays a significant role in the development of DN [ 15 , 16 ]. In mice and rats with DN, a significantly lower expression of the VDR gene has been observed [ 18 ].…”
Section: Animal Studiesmentioning
confidence: 99%
“…Studies in rats and mice have investigated whether supplementation with vitamin D might have a renoprotective role in the process of developing DN [ 15 , 16 , 18 , 19 , 20 , 21 , 22 ]. In the study of Hamzawy et al [ 20 ], 30 diabetic rats were divided into three groups: group 1 (the control group), group 2 (the DN group), and group 3 (the vitamin D-treated DN group).…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation